Review Study on Solar Energy in Bangladesh: Current Status, Challenges, and Future Prospects for Sustainable Development - Al-Noman, Abdullah; Barua, Prabal; Nargis, Nahida; Mohammad, Noor (Global Journal of Earth Science and Engineering, 2025)
This review paper examines the current status, challenges, and future prospects of solar energy development in Bangladesh, with a focus on its integration into sustainable architecture and urban planning. Given Bangladesh’s growing energy demand and vulnerability to climate change, solar energy is highlighted as a key renewable resource for enhancing energy security and reducing greenhouse gas emissions. The paper reviews major solar technologies- including rooftop photovoltaic systems, solar home systems, solar irrigation pumps, floating solar plants, and concentrated solar power-and evaluate their suitability across both urban and rural contexts. Based on a systematic review of recent studies and policy frameworks, the paper identifies major barriers to large-scale solar adoption, such as financial limitations, technical challenges, fragmented policies, and issues related to social acceptance. Despite these obstacles, the review emphasizes the significant social, economic, and environmental benefits of solar energy, including expanded rural electrification, improved public health, and reduced environmental pollutions. The study stresses the need for integrated approaches combining technological innovation, supportive and coherent policy frameworks, financial incentives and active stakeholder participation to accelerate solar energy deployment, particularly in response to Bangladesh’s dense urban environment and climatic constraints. Finally, this study recommends future directions such as advanced energy storage systems, smart grid integration, life-cycle environmental assessments, and evaluation of social impacts. Overall, the paper aims to guide policymakers, researchers, and practitioners toward building a sustainable, resilient, and inclusive solar-powered Bangladesh.
Keywords: Solar energy; Energy efficiency; Climate resilience; Renewable energy policy